Management of Symptomatic Venous Aneurysm - Roberto Gabrielli; Maria Sofia Rosati; Andrea Siani; Luigi Irace (The Scientific World Journal)
Venous aneurysms (VAs) have been described in quite of all the major veins. They represent uncommon events but often life-threatening because of pulmonary or paradoxical embolism. We describe our twelve patients’ series with acute pulmonary emboli due to venous aneurysm thrombosis. Our experience underlines the importance of a multilevel case-by-case approach and the immediate venous lower limbs duplex scan evaluation in pulmonary embolism events. Our data confirm that anticoagulant alone is not effective in preventing pulmonary embolism. We believe that all the VAs of the deep venous system of the extremities should be treated with surgery as well as symptomatic superficial venous aneurysm. A simple excision can significantly improve symptoms and prevent pulmonary embolism.